227k views
3 votes
Given the system of equations. Which of the {-5x+y=6 --> y=5x+6 3x-y=14}

options represents the resulting equation after an equivalent expression for y is substituted into the second equation. 3x - (5x + 6) = 14 -3x + 5x + 6 = 6 3(5x + 6) - y = 14 -3x(5x + 6) + y = 6

User Schmidmt
by
6.7k points

1 Answer

0 votes
The first thing we must do is solve the problem step by step to choose the correct option.
Step 1:
Clear y from the first equation:
-5x + y = 6
y = 5x + 6
Step 2:
Replace this value of y in the second equation:
3x-y = 14
Substituting:
3x- (5x + 6) = 14
answer
the resulting equation after an equivalent expression for y is substituted into the second equation is
3x- (5x + 6) = 14

User Riccardo La Marca
by
5.9k points